Consumer Preference And Outcome Of Purchase Decisions On Branded And Non-Branded Perfumes - Sahul Hameed, Noor Azeema (2014)
The ASEAN countries are having a tropical climate where the condition is hot and humid throughout the year. On the average, Malaysia receives about 6 hours of sunshine per day. In such a hot weather conditions, the sweat combined with the bacteria on the skin may create unnecessary body odour to human. This makes the demand for perfume to a larger extend in Malaysia. The purpose of this study is to identify the purchase characteristics which influencing the purchase decisions on branded and non-branded perfumes. Based on the literature review, the five predictors of purchase characteristics included in the study which may influence the purchase decisions on branded and non-branded perfumes are store image (S l), message framing (MF), perceived quality (PQ), scheme characteristics (SC) and subjective norms (SN). The Stimulus-Organism-Response (S-O-R) model was used to explain the study where the purchase characteristics are stimulus (S), habits as the organism (O) and purchase decisions as the response (R). The present research is a crosssectional study uses primary survey questionnaire method. A total of 164 responses received from the survey questionnaire method. Out of 164 respondents, 81 (49.4%) favoured branded perfumes and 83 (50.6%) preferred non-branded perfumes. The objective of this study is to investigate whether the purchase characteristics influence the purchase decisions on branded and non-branded perfumes with habits as mediating.